173k views
3 votes
Simplify :

a–(b–c)+(m+n)

x+a + (m – 2)

m + (a–k–b)

x + (a–b) – (c–d)

1 Answer

4 votes

Answer:

The simplified expressions are

1) a - b + c + m + n

2) x + a + m - 2

3) m + a - k - b

4) x + a - b - c + d

Explanation:

1) a - (b - c) + (m + n)

To simplify the above expression, we have;

a - (b - c) + (m + n) = a - b - (-c) + m + n = a - b + c + m + n

2) x + a + (m - 2)

To simplify the above expression, we have;

x + a + (m - 2) = x + a + m - 2

3) m + (a - k - b)

To simplify the above expression, we have;

m + (a - k - b) = m + a - k - b

4) x + (a - b) - (c - d) = x + a - b - c -(- d)) = x + a - b - c + d

User Xiao Hanyu
by
5.3k points